Thrombocytopenia after abciximab use results from different mechanisms - Lajus, Sophie; Clofent-Sanchez, Gisèle; Jais, Catherine; Coste, Pierre; Nurden, Paquita; Nurden, Alan (Thrombosis and Haemostasis, 2010)
Our study concerns thrombocytopenia in patients with acute ischaemic coronary artery disease receiving antiplatelet drugs to the αIIbβ3 inte-grin (GPIIb/IIIa). We have screened for drug-dependent antibodies (DDAB) in 18 patients who suffered a fall of > 50% in platelet count (9 patients had a nadir of <50,000 platelets/μl) after receiving abciximab and related results to clinical outcome. Serum or plasma was screened for DDAB using (i) a direct ELISA against purified αIIbβ3, αIIbβ3-abciximab complexes or abciximab alone, (ii) control platelets and flow cytometry and (iii) monoclonal antibody immobilisation of platelet antigens. DDAB were found for 11 patients, with αIIbβ3 ELISA the most sensitive test. Progressive platelet consumption linked with haemoglobin loss and/or use of intra-aortic balloon pumping, another potential cause of a fall in platelet count, was also evaluated. DDAB were identified that recognised αIIbβ3 associated with abciximab and/ or abciximab alone. Screening of both progressive and delayed thrombocytopenia (appearing after 5 to 11 days) suggested that antibodies against abciximab preceded those recognising neo-epitopes on αIIbβ3, with a time-dependent broadening of antibody specificities. Higher titres were seen after second abciximab use. Five antibodies were platelet-activating. In conclusion, the mechanisms responsible for this complication of anti-αIIbβ3 therapy are multiple and often associated with a complex immune response.
Keywords: Coronary syndrome; GPIIb/IIIa; thrombocytopenia; antiplatelet agents; platelet immunology